Budaya Risiko (Risk Culture) Sebagai Pondasi Penerapan Manajemen Risiko Dalam Organisasi - Jose Adrian Simbolon; Nastiar Saputra Rangkuti (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Risk culture is a crucial element in supporting the effectiveness of risk management implementation in organizations. This study aims to analyze the concept of risk culture, its influencing factors, the implementation process, benefits, obstacles, and efforts to improve risk culture within organizations. The study employed a literature review method with a qualitative descriptive approach through analysis of various academic sources, risk management standards, and references related to risk culture. The study results indicate that risk culture plays a significant role in improving risk awareness, decision-making quality, organizational compliance, and business continuity. However, the implementation of risk culture still faces various obstacles such as low employee awareness, resistance to change, weak risk communication, and limited organizational resources. Therefore, management commitment, strengthened communication, ongoing training, and periodic evaluation are required so that risk culture can become an integral part of organizational activities.